Exploração de oportunidades : um estudo junto a empreendedores inseridos em Associações Comerciais do Paraná - Silva, Tayso (2008)
The opportunities identification is considered the first stage of the entrepreneurial process by which all the other stages extend. They are considered in this study, individual and contextual factors that intervened in the opportunities exploitation, beyond the influence of the network environment provided by Trade Associations. The Trade Associations have been chosen as field of study by more factors than the adequacy to the needs of the subject. They are present institutions and consolidated in most cities of the state of Paraná, acting directly in the development of entrepreneurial activity as an entity that supports the entrepreneurial class. The goal of this dissertation is to understand the opportunities exploitation for entrepreneurs in the specific context of Trade Associations of Paraná. This is an exploratory research, with transversal cut, using a qualitative and quantitative approach, according to semistructured interviews, questionnaires and secondary data collection. The results indicate that the main reason for entering into Trade Associations is access to services of credit consulting. The Trade Associations develop actions as partnerships, fairs and studies that favor the opportunities exploitation. They were identified characteristic relationships between entrepreneurs to network affiliates to the same Trade Association. Among the main effects of participation in Trade Associations were diagnosed improving the qualifications of the staff and team of enterprise, increase the number of customers that their business was better known and there was expansion in their consumer markets. They were found opportunities exploited by entrepreneurs after the entry into Trade Associations, as the launch of a new product or service, the opening of new ventures and the formation of partnerships among members. It was concluded that the intensity of the effects of actions and in the context of networks offered by Trade Associations is also related to the intensity of the entrepreneur's participation. The Trade Associations have proved productive contexts for the formation of networks of relationships among affiliates, opening up space to exploit new opportunities through these relationships. The membership time is a variable that don't shows significant relationship, except for increasing number of entrepreneur's employers and for the Trade Association's support for municipal festivities as action that encourages the opportunities exploitation and two types opportunities exploitation: The expansion of the onsumer market and the increasing of number of customers. They were diagnosed exploited opportunities by affiliates influenced by participation in the Trade Associations, corroborating the importance of the context of Trade Associations to exploit opportunities.